Queer Between the Covers Histories of Queer Publishing and Publishing Queer Voices - Kassir, Leila; Espley, Richard (University of London Press, 2021)
Queer Between the Covers presents a history of radical queer publishing and literature from 1880 to the modern day. Chronicling the gay struggle for acceptance and liberation, this book demonstrates how the fight for representation was often waged secretly between the covers of books at a time when public spaces for queer identities were limited. The chapters provide an array of voices and histories - from the famous, Derek Jarman and Oscar Wilde, to the lesser-known and underappreciated John Wieners and Valerie Taylor. It includes first-hand accounts of seminal moments in queer history, including the birth of Hazard Press and the Defend Gay's the Word Bookshop campaign in the 1980s. The book demonstrates how the queer community could be brought together through shared literature. The works discussed show the imaginative and radical ways in which queer texts have fought against censorship and repression and could be used as a tool for political organisation and production. From the powerful community-wide demonstrations for Gay's the Word during their battle with the British government, the mapping of Chicago's queer spaces within Valerie Taylor's pulp novels, or the anonymous but likely shared authorship of the 19th-century queer text Teleny. Queer publishing often involved a range of creative tactics to beat the censor, from self-publishing to anonymous authorship. The book also shows how collage and the repurposing of found image and text became a key queer publishing practice, from Derek Jarman's vast creative repertoire to book artwork created by the Hazard Press. A fascinating and poignant analysis of some key historic moments for queer lib in publishing and book history, this is an essential read for those interested in how LGBTQ people throughout modernity have used literature as an important forum for self-expression and self-actualisation when spaces and sites for queer expression were taboo.